2021
DOI: 10.3390/cancers13061426
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Is a Predictive Biomarker in Patients with Epidermal Growth Factor Receptor (EGFR) Mutated Advanced Non-Small Cell Lung Cancer (NSCLC) Treated with Tyrosine Kinase Inhibitor (TKI) Therapy

Abstract: Background: First-line treatment for patients with non-small cell lung cancer (NSCLC) with a sensitizing epidermal growth factor receptor (EGFR) mutation is a tyrosine kinase inhibitor (TKI). Despite higher response rates and prolonged progression free survival (PFS) compared with platinum doublet chemotherapy, a subset of these patients do not receive prolonged benefit from these agents. We investigate if the neutrophil-to-lymphocyte ratio (NLR) and other markers of cachexia and chronic inflammation correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…In contrast to a previous study (35), the present univariate analysis suggested that number of metastases and mutation status were associated with PFS and OS estimates. In clinical practice, patients with multiple metastases tend to be in poor overall health, have advanced disease and poor previous treatment response, as well as high toxicity susceptibility.…”
Section: Univariate Analysis Multivariate Analysiscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to a previous study (35), the present univariate analysis suggested that number of metastases and mutation status were associated with PFS and OS estimates. In clinical practice, patients with multiple metastases tend to be in poor overall health, have advanced disease and poor previous treatment response, as well as high toxicity susceptibility.…”
Section: Univariate Analysis Multivariate Analysiscontrasting
confidence: 99%
“…Circulating neutrophils promote tumor growth and metastasis through tumor inflammatory mediators (arginine and nitric oxide). NLR values have been shown to have prognostic relevance in various types of cancer, including NSCLC ( 35), esophageal cancer (32) and pelvic malignancies (36). In the present study, higher NLR values were associated with poorer PFS (mPFS, 5.73 vs. 9.17 months) and OS (mOS, 12.03 vs. 26.33 months) in the H-NLR group compared with in the L-NLR group.…”
Section: Discussionsupporting
confidence: 50%
“…It promotes tumor-promoting activities, including angiogenesis, mutagenesis, and immunosuppression [ 10 ]. Hematological parameters, such as the neutrophil-to-lymphocyte ratio (NLR) and systemic inflammation index (SII), have prognostic roles in various malignancies, including lung cancer, as potential cancer inflammation-induced biomarkers [ 11 , 12 , 13 , 14 , 15 , 16 ]. These peripheral blood parameters are of notable interest because of their easy and ready accessibility in clinical practice [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has previously revealed that blood-based inflammatory/immune markers, including lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) are significant prognostic indicators of NSCLC [ 12 , 13 , 14 , 15 ]. These hematological markers can be detected inexpensively and conveniently in clinical practice and could possibly reflect tumor-promoting activities [ 16 ].…”
Section: Introductionmentioning
confidence: 99%